Conceptual Design of Life-Detecting Experiment for Future Europa Lander Mission - Nuri Park; Yu Yi (Journal of Astronomy and Space Sciences, 2018)
A previous exo-terrestrial life-detecting experiment, which was conducted on Mars, sought to detect the products of glucose metabolism, the most common biological process on Earth (Viking biological experiment). Today, glucose metabolism is not considered the universal process of life survival. As NASA plans to launch an orbiter mission in the near future (2020s, the Clipper) and ultimately conduct a lander mission on Europa, a detection experiment that can give broader information regarding habitability is highly required. In this study, we designed a life-detecting experiment using a more universal feature of life, the amphipathic molecular membrane, theoretically considering the environment of Europa (waterdominant environment). This designed experiment focuses on finding and profiling hydrophobic cellular membrane-like microstructures. Expected results are given by conceptual data analysis with plausible hypothetical samples.